El camino hacia una economía verde: el caso de la infraestructura de turismo en áreas naturales protegidas - Barrantes, Roxana (2013)
This paper examines the definition of Green Economy and discusses the potential of the tourism sector to serve as a success case story to implement the principles of this development model. To attain this goal, we focus on the tourism regulatory framework, mainly in the infrastructure needed to develop tourism activities on these areas, and then provide policy recommendations in order to remove the perverse incentives present in the current regulations, which could threaten the conservation of natural resources and the ecosystem services that they provide to society.